Pretreatment with Magnesium Sulfate to Alleviate Pain on Propofol Injection: A Prospective Randomized Double Blind Study - Hossain, Muhammad Sazzad; Rashid, Md Mamunur; Rashid, Mohammad Mamunur; Babu, Md Anisur Rahman; Sultana, Afsana; Saha, Devashis; Hasan, Mohammad IftaKhiarul (Mediscope, 2019)
Background and aim of study: Propofol is one of the most frequently used medications for inducing and maintaining anesthesia. However, propofol injection causes pain and discomfort in more than 70% of patients. This study was performed to determine the effect of magnesium sulfate on reducing pain at the onset of anesthesia induced by propofol injection. Materials and methods: A total of 80 healthy adult patients were selected in this study with either sex, scheduled for routine elective surgical procedure under general anesthesia. The patients enrolled were divided randomly into two groups of 40 patients each. Group I received 30 mg/kg of intravenous magnesium sulfate in 5 ml. Group II (placebo group) received 5ml of 0.9% intravenous normal saline 1 minute before propofol injection. The patients were asked to report their pain during injection of propofol. For all statistical tests, p<0.05 was taken to indicate a significant difference. Results: The incidence of pain experienced in magnesium sulfate group was 30% patients and in saline group was 60% patients, which is statistically significant p<0.05. The severity of POPI was also lower in magnesium sulfate group than the saline group (p<0.05). The incidence of mild and moderate pain in groups I versus group II was 22.5% versus 37.5% and 7.5% versus 22.5% respectively p<0.05. There was no severe pain recorded in any groups. Conclusion: Magnesium sulfate can be used before induction of anesthesia to reduce pain on propofol injection. Mediscope Vol. 6, No. 2: Jul 2019, Page 73-77